Development of Performance Assessment Inspection Visual of Acetic Acid (Iva) - Hariyati, Tri; Ratna Rahayu, Sri; Khumaedi, M. (Journal of Research and Educational Research Evaluation, 2018)
Instruments that have valid and reliable scoring guidelines will provide learning evaluation results that match the achievements of social science lesson competencies. This study aims to determine the validity and reliability of the standard essay test instruments to measure the higher order thingking skills of social science of the 8th grade junior high schools developed. This study uses research and development techniques to produce standard essay test instruments using 30 samples on a small-scale test and 105 samples on a large-scale test taken at random. The study used nine steps of instrument development that is 1) compile test specification; 2) write test questions; 3) reviewing test questions; 4) test the test; 5) analyze the items; 6) improve the test; 7) assemble the test; 8) carry out tests; 9) interpret the test results. Data collection techniques used interview techniques, document studies, and tests. The results showed that the instrument has Aiken's V> 0.3, the mean value has a value of 0.8. Estimation of instrument reliability at small scale test is 0.788, large scale test is 0.819 and final test for 12 items is 0.918. The results showed that standard essay test instruments to measure higher order thingking of social skills of junior high school in 8th grade proved to be valid and reliable.